Male-mediated introgression of Bos indicus genes into Argentine and Bolivian Creole cattle breeds - Giovambattista, Guillermo (2000)
The geographic distribution and frequency of Bos taurus and Bos indicus Y chromosome haplotypes amongst Argentine and Bolivian Creole cattle breeds were studied, using cytogenetic and molecular genetic techniques. A complete correspondence between Y chromosome morphology and the haplotype of the Y-linked microsatellite marker INRA 124 was found in all males examined. The taurine and indicine haplotypes were detected in 85-7 and 14-3% of the males studied, respectively, although these frequencies varied amongst the different breeds examined. The geographic distribution of this polymorphism suggests a pattern of zebu introgression in South America. The highest frequencies of the Zebu Y-chromosome are found in Brazilian populations (43-90%), in the eastern part of the continent, while it is absent in the southermost breeds from Uruguay and Argentina. Bolivan breeds, at the centre of the continent, exhibit intermediate values (17-41%). This east/west and north/south gradient of male Zebu introgression could be explained by historical events and environmental factors.